2017
DOI: 10.3389/fpls.2017.00914
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Critical Function of Sucrose Metabolism Related-Enzymes in Starch Accumulation in the Storage Root of Sweet Potato

Abstract: The starch properties of the storage root (SR) affect the quality of sweet potato (Ipomoea batatas (L.) Lam.). Although numerous studies have analyzed the accumulation and properties of starch in sweet potato SRs, the transcriptomic variation associated with starch properties in SR has not been quantified. In this study, we measured the starch and sugar contents and analyzed the transcriptome profiles of SRs harvested from sweet potatoes with high, medium, and extremely low starch contents, at five development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 55 publications
4
51
1
Order By: Relevance
“…Elsewhere, the close association of carbohydrate metabolism with storage root development was also revealed on Lycoris sprengeri [20], sweet potato (Ipomoea batatas.) [32], and Sagittaria sagittifolia [33]. Altogether, these ndings con rmed the important role of starch and sucrose metabolism in bulb formation and development of bulbous plants via transcriptome pro ling method.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Elsewhere, the close association of carbohydrate metabolism with storage root development was also revealed on Lycoris sprengeri [20], sweet potato (Ipomoea batatas.) [32], and Sagittaria sagittifolia [33]. Altogether, these ndings con rmed the important role of starch and sucrose metabolism in bulb formation and development of bulbous plants via transcriptome pro ling method.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, Zhang et al [32] found that AGPase, soluble starch synthase, granule-bound starch synthase and SuSy encoding genes mostly peaked in sweet potatoes at 95 d after planting when starch accumulation peaked. Apparently, the genes mainly responsible for starch accumulation varies with plant type.…”
Section: Gene Expression During Corm Developmentmentioning
confidence: 99%
“…CL3807.Contig32_All (Fig 4j). Several enzymes including granule-bound starch synthase (GBSS), starch branching enzyme (SBE) and UDP-glucose pyrophosphorylase (UDPGP), are pivotal in sweet potato starch biosynthesis [60][61][62]. Unigene35652_All and Unigene49607_All related to GBSS were significantly upregulated in the MTRs and LTRs stages of tuberous root development in our work ( Fig.…”
Section: Down-regulated Of Lignin Biosynthesis and Up-regulated Of Camentioning
confidence: 62%
“…Invertase genes also showed differential expression between non-infected and infected plants. A cell wall invertase unigene was upregulated in infected plants, but three vacuolar invertase genes, including the previously reported sweet potato vacuolar invertase genes Ibβfruct2 and Ibβfruct3 [19,20], were downregulated. Furthermore, genes for a plastid glucose transporter (GT) showed downregulated expression in the infected plants, and several other sugar transporter genes were DEGs.…”
Section: Spvd Affects the Expression Levels Of Genes Involved In Carbmentioning
confidence: 75%
“…Based on the RPKM values observed, genes differentially expressed between S14 and H14 were screened by comparing the two libraries based on the combined criteria of q-value (false discovery rate (FDR)) of <0.01 and absolute fold change of RPKM > 2. The differential expression of target genes was validated using the qRT-PCR method described previously [20].…”
Section: Unigene Expression Analysis and Differentially Expressed Genmentioning
confidence: 99%